Localized Gastric Amyloidosis with Kappa and Lambda Light Chain Co-Expression - Yong Hwan Ahn; Ye Young Rhee; Suck Chei Choi; Geom Seog Seo (Korean Society of Gastrointestinal Endoscopy, 2018)
Esophagogastroduodenoscopy for cancer screening was performed in a 55-year-old woman as part of a health screening program, and revealed a depressed lesion approximately 20 mm in diameter in the lesser curvature of the mid-gastric body. Several biopsy specimens were collected as the lesion resembled early gastric cancer; however, histopathologic evaluation revealed chronic active gastritis with an ulcer and amorphous eosinophilic material deposition. Congo red staining identified amyloid proteins, and apple-green birefringence was shown using polarized light microscopy. Immunohistochemical staining revealed the presence of kappa and lambda chain-positive plasma cells. There was no evidence of underlying plasma cell dyscrasia or amyloid deposition in other segments of the gastrointestinal tract. Echocardiography and computed tomography of the chest, abdomen, and pelvis did not show any significant findings. Thus, the patient was diagnosed with localized gastric amyloidosis with kappa and lambda light chain coexpression.